Ocular manifestations in Iranian patients referred to rheumatology clinics from 2018 to 2020 - Meharan Pournazari; Tara Hashemi; Mahsa Zarpoosh; Parsa Amirian (Immunity, Inflammation and Disease)
Abstract Aim Autoimmune diseases are presented with many signs and symptoms. Eyes are commonly involved in these diseases. This study aimed to estimate the prevalence of different ophthalmological complications in patients with and without immune‐mediated rheumatological diseases. Methods Patients who were referred to Kermanshah's rheumatologic clinics by an ophthalmologist from 2018 to 2020 for a rheumatologist visit were included. A checklist for extracting data from medical files; containing symptoms, organ involvement, ocular diseases diagnosed by an ophthalmologist, rheumatologic diseases diagnosed by a rheumatologist, lab tests, and disease progression was created. After we evaluated the medical data, we found that 54 patients out of 106 were diagnosed to have immune‐mediated rheumatological diseases. Patients were divided into two groups; the first group included patients with diagnosed immune‐mediated rheumatologic disease and ophthalmic complications; patients with no known immune‐mediated rheumatological disease were considered the second group. The obtained information was analyzed using statistical tests. Results One hundred and six patients participated in this study, 67% of whom were females. The most common ocular symptom was blurred vision (49%). Involvement of both eyes (43.4%) was more common than single left or right eye involvement. The most common ophthalmic disease was anterior uveitis (35.8%). The most common rheumatologic disease was Behçet's disease (21.7%). Hypertension and hypothyroidism were the most common comorbidities; 36.7% of the patients had skin and mucous involvement, and 37.7% had joint involvement. In follow‐up of the ophthalmic symptoms, most patients were controlled partially. Ophthalmic diseases, laboratory tests, joint involvement, skin and mucous involvement, and lung involvement were associated with rheumatologic diseases. Conclusion Early diagnosis of ocular involvement in rheumatologic diseases is crucial to prevent adverse complications. The results can be beneficial for a better perception of ophthalmic symptoms and diseases among patients with autoimmune diseases.